The investigation of antioxidant and antidiabetic activities of Christia vespertilionis leaves extracts - Murugesu, Suganya; Perumal, Vikneswari; Balan, Tavamani; Fatinanthan, Sharon; Khatib, Alfi; Arifin, Norfarahanum Juhar; Mohd Shukri, Nur Syafiqah Salma; Saleh, Mohammed S.M.; Hin, Lee Wing (Elsevier B.V., 2020)
The present study has been aimed to investigate the antioxidant and antidiabetic activities of Christia vespertilionis leaves extracts. The analysis of the extracts obtained using different solvents revealed that ethyl acetate: methanol extract as the most potential in 2, 2- diphenyl-1-picrylhydrazyl (DPPH) radical scavenging while hexane: ethyl acetate exhibited highest ferric reducing antioxidant power (FRAP) capacity and a-glucosidase inhibition. The infrared analysis displayed the presence of O-H, C-H, C=O, C=C, C-O, and N-H predominantly in the extracts reflecting some of the compounds reported previously; quercetin 3-O-glucoside, oleanolic acid methyl ester, b-sitosterol, stigmasterol, geraniol and 2’-hydroxygenistein. The latter two displayed competitive mode of inhibition in both the yeast and human protein receptors. Conclusively, C. vespertilionis leaves contain potent antioxidants and a-glucosidase inhibitors; thus, further studies can enhance its use in pharmaceutical applications.